Perineum Spindle Cell Sarcoma in Neurofibromatosis Type 1 - Sanjeev Sandrasecra; Senthil Vasan; Fitjerald Henry; Salmi Abdullah; Mohd Nizam Md Hashim; Siti Rahmah Hashim Isa Merican; Michael Pak-Kai Wong (Oman Medical Journal, 2023)
Soft tissue neoplasm is common among patients with neurofibromatosis type 1 (NF-1). We present a case of a middle-aged woman with NF-1 who presented with a painless, insidiously increasing perineal mass for the past eight months. She underwent colonoscopy, computed tomography staging, magnetic resonance imaging of the pelvis, core-needle biopsy, and later wide local excision of left perineum swelling. Histopathological examination showed a high-grade spindle cell sarcoma, which is a rare association among NF-1. Spindle cell sarcoma is a group of malignant soft tissue tumors with locally destructive growth with spindle-shaped neoplastic cells. The solitary spindle cell sarcoma of the perineum is rare, and wide local resection with a clear margin is the only treatment at present—the scarcely available evidence limiting the use of adjuvant chemotherapy, immunotherapy, and radiotherapy.